Różnice w poziomie gotowości szkolnej 6-letnich dziewczynek i chłopców ze specjalnymi potrzebami edukacyjnymi. Komunikat z badań - Buchnat, Marzena (Wydawnictwo Naukowe UAM, 2013)
In the context of the ongoing debate about a compulsory lowering of school age, which results from the assumptions of the education system reform, we would like to pay special attention to the well-known but paradoxically rarely discussed problem of different levels of readiness, experience and school achievements of children on grounds of gender. We asked to what extent boys and girls are similar/different in terms of their school maturity level and the level of school adaptation, while taking into account the risk factors which are special educational needs (SEN). We map the research results presented on pedagogical theory and practice of school failure diagnosis and proceed to a discussion on the impact of cultural patterns of gender roles, gender stereotypes and the process of socialization and education on boys’ and girls’ preparation for school requirements.
Gender differences in school readiness of 6-year-old girls and boys with special educaeducational needs. Research paper
Keywords: special educational needs; school adaptation; school readiness; gender and education; gender stereotypes